2023
DOI: 10.3389/fmicb.2023.1280026
|View full text |Cite
|
Sign up to set email alerts
|

Secondary pulmonary infection and co-infection in elderly COVID-19 patients during the pandemics in a tertiary general hospital in Beijing, China

Chaoe Zhou,
Yaping Jiang,
Liying Sun
et al.

Abstract: BackgroundMost people are infected with COVID-19 during pandemics at the end of 2022. Older patients were more vulnerable. However, the incidence of secondary bacterial, fungal or viral pulmonary infection and co-infection is not well described in elderly hospitalized COVID-19 patients.MethodsWe retrospectively reviewed the medical records of all elderly (≥65 years) hospitalized patients with laboratory-confirmed COVID-19 from December 1, 2022 to January 31, 2023. Demographics, underlying diseases, treatments,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Aspergillus fumigatus is the most common species in the Aspergillus genus, but fungal infections often have few notable characteristics and the pathogen may not be detectable for a long time. Therefore, diagnosing fungal infections in patients with normal immune function can be challenging, especially as age increases and immune function declines ( Zhang et al., 2014 ; Zhou et al., 2023 ). A multicenter retrospective study has shown that virus reactivation is associated with an increased risk of mortality in patients ( Huang et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Aspergillus fumigatus is the most common species in the Aspergillus genus, but fungal infections often have few notable characteristics and the pathogen may not be detectable for a long time. Therefore, diagnosing fungal infections in patients with normal immune function can be challenging, especially as age increases and immune function declines ( Zhang et al., 2014 ; Zhou et al., 2023 ). A multicenter retrospective study has shown that virus reactivation is associated with an increased risk of mortality in patients ( Huang et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%